POLYSEMY AND MONOSEMY IN THE ORIGIN OF ECOLOGICAL TERMS IN THE AZERBAIJANI LANGUAGE - Nurlana Fakhreddin kyzy, Abdullaeva (Өзбекстан Республикасы Илимлер Академиясы Қарақалпақстан бөлиминиң ХАБАРШЫСЫ, 2024)
Speaking about the presence of polysemy and unambiguity in the role of environmental terms, linguists note that in any case, the forms here are created by changing words and terms. By changing the meanings of terms, new terms appear. In such a situation, the semantic method is considered as one of the calculations of newly emerging, developing concepts. It is clear that any word and terminological system that deviate from the meaning or are subject to polysemy become the basis for representatives of new concepts and expressions. In the situation of such new concepts, it creates new lexical-semantic combinations, acquiring additional meanings in addition to the original ones. In the activity and formation of environmental terms, this method is used more widely.